Beauty or not beauty: Making up the producer of popular culture. (June 2017) - Dambrin, Claire; Lambert, Caroline
Abstract: Popular culture and the institutions and rituals that make it possible have become overwhelmingly significant in modern life. In this paper, we draw upon governmentality studies to explore the making-up (du Gay et al., 1996) of brand managers in a leading international cosmetics firm. Through in-depth interviews and participant observation, we analyse the control mechanisms through which brand managers embody their product and are made consumer subjects inside their own organisation. Illustrating how these key intermediaries of popular culture become "simultaneously promoters of commodities and commodities they promote" (Bauman, 2007), we not only account for the control practices in use in a key organisation related to popular culture, but also investigate how certain control practices shape the very site of popular culture.